From Isolation to Collapse: Environmental Contributions to Complex Trauma in Thirteen Reasons Why - Endarina Sukmawati; Prayudias Margawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study explores the representation of adolescent trauma through the character of Hannah Baker in Thirteen Reasons Why by Jay Asher. Using a qualitative descriptive method with a psychological literary analysis approach, the research applies Bronfenbrenner’s Ecological Systems Theory and the concept of complex trauma to investigate how environmental systems contribute to psychological deterioration. The analysis identifies five levels microsystem, mesosystem, exosystem, macrosystem, and chronosystem that each fail to provide the support Hannah needs, ultimately leading to her emotional collapse. Key findings reveal that direct peer betrayal, institutional neglect, weak family-school communication, cultural normalization of victim-blaming, and cumulative unresolved trauma collectively influence the protagonist's declining mental health. The study demonstrates that trauma in adolescence is rarely the result of a single incident but rather the accumulation of systemic failures over time. The findings imply that educational institutions and communities must adopt trauma-informed frameworks and foster empathetic, interconnected support systems to protect vulnerable youth.